Hydroxyurea selection for enhancement of homology-directed targeted integration of transgenes in CHO cells - Kwak, Jin Myeong; Lee, Youngsik; Shin, Sung Wook; Lee, Jae Seong (New Biotechnology, 2021)
Site-specific integration via genome editing technologies has been implemented in Chinese hamster ovary (CHO) cells for predictable and efficient cell line development and engineering. Various strategies have been employed to enhance knock-in (KI) efficiency for precise homology-directed repair (HDR)-mediated targeted integration of transgenes in CHO cells. Given the cell cycle-dependent regulation of the DNA damage repair pathway, cell cycle synchronization to the HDR-favored S/G2 phase has been successfully utilized in mammalian cells, but the effect is limited in CHO cells. Here, we describe a cell cycle enrichment method to increase HDR-mediated KI efficiency in CHO cells. Existing G1 cell cycle synchronization methods showed transient cell cycle arrest and did not improve KI efficiency. Rather than cell cycle arrest with a high concentration of chemicals followed by a release step, cells were incubated in the presence of a lower concentration of hydroxyurea (HU) to enrich cells in the S phase. HU selection allowed for robust S phase enrichment of CHO cells by up to 70 % and maintained cell viability. This short-term selection resulted in improved KI efficiency by 1.2–1.5 fold compared with cells in the control condition. Overall, this approach serves as a simple and effective strategy for enhancement of site-specific genome engineering in CHO cells.
Keywords: Cell viability; Cell-cycle arrest; Chinese Hamster ovary cells; Editing technology; Genome engineering; Mammalian cells; Site-specific; Synchronization method; Animals; Cell Cycle; CHO Cells; Cricetulus; Gene Editing; Genetic Engineering; Hydroxyurea; Cell cycle; CHO cells; CRISPR/Cas9; Hydroxyurea; Targeted integration